Penerapan Hazard Analysis Critical Control Point pada Proses Produksi Udang Cooked Peeled Tail On Di PT. X - Sari, Lutfita; Nugroho, Sigit Dwi; Yuliati, Nuriah (Technomedia Journal, 2023)
Hazard Analysis Critical Control Point (HACCP) is one of the standards set to ensure food safety by analyzing the potential hazards that occur in the production process of food products. The application of HACCP is an effort to control the quality of the final product so that it meets the established standards, namely safe for consumption and quality. PT. X is a fishery company that produces CPTO (cooked peeled tail on) white shrimp. This company has implemented HACCP in its production process. The purpose of this study was to analyze the application of HACCP in the CPTO vaname shrimp production process at PT. X. The data analysis method used is descriptive analysis method with an evaluative approach. There are 12 stages of HACCP implementation including the formation of a HACCP team, product descriptions, product use objectives, preparation of production flow charts, confirmation of flow charts in the field, hazard identification, determination of CCPs, determination of critical limits for each CCP, monitoring of CCPs, determination of corrective actions, determination of verification procedures as well as documentation and recording. The results showed that based on the 12 points of HACCP implementation stages implemented by PT. X in the CPTO (cooked peeled tail on) vaname shrimp (Litopenaeus vannamei) production process has all complied with SNI 01-4852-1998.